2019
DOI: 10.2152/jmi.66.50
|View full text |Cite
|
Sign up to set email alerts
|

Encounter of Pepper-CPGE for the elderly and patients with schizophrenia: an innovative strategy to improve patient's recreation, rehabilitation, and communication

Abstract: In Japan, humanoid robots has been introduced in the medical and elderly care environment. The application program of Care Prevention Gymnastics Exercises for Pepper (Pepper-CPGE) made by Xing Company, Japan is a body-brain gymnastics recreation program for 40 minutes tailored to the elderly's functional level. It consists of moving, watching/healing, and playing. "Move the body" exercise and other active range of motion activities are done according to the music. Pepper-CPGE was introduced as a clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Specifically, there were 51 articles pertaining to research question 1, 98 articles pertaining to research question 2, and 16 articles pertaining to research question 3; however, it is important to note that some articles addressed multiple research questions. The results included all types of studies (quantitative, qualitative, mixed method, systematic reviews, and scoping reviews) as well as gray literature including reports, editorials, and opinion pieces ( Multimedia Appendix 3 provides more details [ 2 , 13 , 14 , 18 , 21 , 27 - 152 ]). A total of 16 included articles were also cited in the systematic and scoping reviews that were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, there were 51 articles pertaining to research question 1, 98 articles pertaining to research question 2, and 16 articles pertaining to research question 3; however, it is important to note that some articles addressed multiple research questions. The results included all types of studies (quantitative, qualitative, mixed method, systematic reviews, and scoping reviews) as well as gray literature including reports, editorials, and opinion pieces ( Multimedia Appendix 3 provides more details [ 2 , 13 , 14 , 18 , 21 , 27 - 152 ]). A total of 16 included articles were also cited in the systematic and scoping reviews that were included.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging AIHTs discussed in the literature included robots (eg, socially assistive robots [SARs], humanoid robots, and mobility robots), predictive analytics, clinical decision support systems (CDSSs), smart homes, and virtual health care assistant chatbots. It was found that nurses are already using robots in their clinical practice, across multiple patient populations, for various tasks, such as to assist with exercise sessions for older adults or rehabilitation patients [ 27 , 28 ]; to serve as a distraction tool for pain management [ 29 - 31 ]; and to facilitate conversation and rapport, conduct interviews, and deliver patient education [ 27 , 33 , 34 , 36 - 39 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 studies developed living lab settings (Bedaf et al, 2018;Cavallo et al, 2018;Heerink et al, 2009Heerink et al, , 2010Torta et al, 2014;Wade et al, 2011;Wu et al, 2014). 8 studies investigated different forms of group exercises (Bradwell et al, 2019;Lewis et al, 2016;Miyachi et al, 2017;Moyle et al, 2016;Robinson et al, 2016;Šabanović et al, 2013;Ujike et al, 2019;Kazuyoshi Wada et al, 2005;Wada et al, 2006) and one study investigated individual interaction (Pu et al, 2020). Methodologies included explorative qualitative research approaches, descriptive and correlative quantitative approaches, and different mixed-methods methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…Especially the perception of a social presence, for example, through humanoid appearance and users' ability to interact seems to be important (Heerink et al, 2009(Heerink et al, , 2010Pu et al, 2020). Perceiving a social dimension in the interaction is not only preferred by the users but is also shown to increase the accessibility as the perceived ease of use in interacting with SATs (Heerink et al, 2009;Torta et al, 2014;Ujike et al, 2019).…”
Section: Mixed Methodsmentioning
confidence: 99%
See 1 more Smart Citation